Diversity of ectoparasitic bat flies (Diptera, Hippoboscoidea) in inter-Andean valleys: evaluating interactions in the largest inter-Andean basin of Colombia - Camila López-Rivera; Laura Natalia Robayo-Sánchez; Alejandro Ramírez-Hernández; Jerson Andrés Cuéllar-Saénz; Juan Diego Villar; Jesús Alfredo Cortés-Vecino; Fredy A. Rivera-Páez; Paula Andrea Ossa-López; Erika M. Ospina-Pérez; Jose J. Henao-Osorio; Alexandra Cardona-Giraldo; Javier Racero-Casarrubia; et al. (ZooKeys, 2024)
Flies belonging to the families Streblidae and Nycteribiidae are highly specialized arthropods that feed on the blood of bats. Their morphology varies and has adapted throughout their coevolutionary history with hosts. Bat flies are often associated with specific bat species and can establish distinct infracommunities. Interaction networks have been used to better understand these associations, revealing interaction modules between bats and their parasites. The Magdalena River basin is the largest in Colombia, encompassing a wide variety of climatic and ecological conditions, with up to 98 bat species reported. We conducted field trips to capture bats and bat flies in different locations along the basin and reviewed literature records and biological collections to gather additional data on interactions between bats and bat flies in this region. We found a high diversity of bats and bat flies in the Magdalena River basin, revealing a medium specialization and modularity in these interactions. We identified bat fly infracommunities and negative associations between certain bat fly species, suggesting competition for resources within hosts. The specialization is similar to that reported in degraded and fragmented habitats where the availability of shelters decreases, favoring the overcrowding of bats, forming multi-species colonies. In conclusion, our study provides important information on the interactions between bats and bat flies in the Magdalena River basin, expanding knowledge about the diversity and structure of these communities in inter-Andean landscapes.